2022
DOI: 10.1371/journal.pwat.0000025
|View full text |Cite
|
Sign up to set email alerts
|

Advances on water quality modeling in burned areas: A review

Abstract: Wildfires are a recurring hazard in forested catchments representing a major threat to water security worldwide. Wildfires impacts on water quality have been thoroughly addressed by the scientific community through field studies, laboratory experiments, and, to a lesser extent, the use of hydrological models. Nonetheless, models are important tools to assess on-site and off-site wildfires impacts and provide the basis for post-fire land management decisions. This study aims to describe the current state of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…Water providers, reservoir operators, land managers, and emergency response agencies would benefit from improved assessment and prediction of the character, magnitude, and duration of waterquality impacts after wildfire in watersheds across a wide range of ecoregions. A lack of adequate pre-and post-wildfire water-quality data hinders model calibration and adaptation (Basso et al, 2022), assessment of post-wildfire recovery (Hampton et al, 2022), and understanding how wildfires will affect regulatory requirements (Paul et al, 2022). Here we describe a path forward for strategic, consistent post-wildfire water-quality data collection for surface water that, when deployed across a range of ecosystems, will lead to vastly improved assessment and prediction of impacts of wildfire on water supplies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Water providers, reservoir operators, land managers, and emergency response agencies would benefit from improved assessment and prediction of the character, magnitude, and duration of waterquality impacts after wildfire in watersheds across a wide range of ecoregions. A lack of adequate pre-and post-wildfire water-quality data hinders model calibration and adaptation (Basso et al, 2022), assessment of post-wildfire recovery (Hampton et al, 2022), and understanding how wildfires will affect regulatory requirements (Paul et al, 2022). Here we describe a path forward for strategic, consistent post-wildfire water-quality data collection for surface water that, when deployed across a range of ecosystems, will lead to vastly improved assessment and prediction of impacts of wildfire on water supplies.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, because wildfires can reduce the threshold precipitation intensity at which overland flow occurs, post-wildfire stream discharge and sediment concentrations can be orders of magnitude greater than they would have been for similar storms pre-wildfire (Wondzell and King, 2003;Murphy et al, 2015), which poses challenges to current monitoring capabilities. As a result of these challenges, there are numerous gaps in post-wildfire water-quality data (Yu and Cheng, 2008;Rust et al, 2018;Basso et al, 2022;Hampton et al, 2022;Paul et al, 2022;Robinne et al, 2022;Raoelison et al, 2023), as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Data-driven models often have lower data requirements than physical models, offering a unique opportunity to deepen understanding 16 . Studies using these techniques for post-fire water quality analysis 4,[29][30][31][32][33][34][35] have been relatively narrow in scope, for example, neglecting sediment, DOM, and nutrient responses across western U.S. Here, we apply data-driven methods to quantify postfire water quality signals across a wide range of constituents, evaluating a large sample of watersheds over several decades.…”
mentioning
confidence: 99%
“…It is hypothesized that the key model input that represents fire in the GBR water quality models (in lieu of a model specifically adapted for fire) is the remotely sensed seasonal ground cover dataset, used to represent the cover factor (C-factor) in the calculation of hillslope erosion via the Revised Universal Soil Loss Equation (RUSLE). Land cover change is the most widely applied water quality model adaptation to represent fire impacts (Basso et al, 2022).…”
mentioning
confidence: 99%